Performing information governance : a step-by-step guide to making information governance work - Giordano, Anthony David (IBM Press, 2015)
Using case studies and hands-on activities, this book discusses topics in information governance (IG): recognizing hidden development and operational implications of IG--and why it needs to be integrated in the broader organization; integrating IG activities with transactional processing, BI, MDM, and other enterprise information management functions; the information governance organization: defining roles, launching projects, and integrating with ongoing operations; performing IG in transactional projects, including those using agile methods and COTS products; bringing stronger information governance to MDM: strategy, architecture, development, and beyond; governing information throughout the BI or big data project lifecycle; performing ongoing IG and data stewardship operational processes; auditing and enforcing data quality management in the context of enterprise information management; maintaining and evolving metadata management for maximum business value. --